فلسفة سياسات التعليم الأخضر ومتطلباته في الجامعات السعودية رؤية تربوية مقترحة وفق تصنيف جرين ماتريكس - Bajaber, Samera Salem (IIUM Journal of Educational Studies, 2025)
The study aimed to reveal the philosophy of green education policies and its requirements in Saudi universities, a proposed educational vision according to the Green Matrix classification, and the study used the descriptive approach, and the study resulted in a number of results, including: that green education is an urgent necessity to confront the challenges of climate change, and it is a type Education comes simultaneously with the great technological development and with the broad and complex digital transformation in all institutions and companies within society. And that green education in general has a great Islamic dimension due to the interest of many legal texts and jurisprudential rulings, in everything that would rebuild the earth and preserve its safety and health from anything that threatens the lives of living organisms in it, and that one of the requirements of green education is to include the philosophy of the educational policies of universities. Saudi Arabia, in line with the philosophy of green education, and the requirement to intensify financial funding for research and scientific chairs related to the environment, and to provide laboratories equipped with the latest technological systems, and experts in renewable energy to train researchers in the use of environmentally friendly products, presenting a proposed educational vision according to the Green Matrix classification.